Diversity in thermal affinity among key piscivores buffers impacts of ocean warming on predator–prey interactions. (28th August 2017) - Selden, Rebecca L.; Batt, Ryan D.; Saba, Vincent S.; Pinsky, Malin L.
Abstract: Asymmetries in responses to climate change have the potential to alter important predator–prey interactions, in part by altering the location and size of spatial refugia for prey. We evaluated the effect of ocean warming on interactions between four important piscivores and four of their prey in the U.S. Northeast Shelf by examining species overlap under historical conditions (1968–2014) and with a doubling in CO2 . Because both predator and prey shift their distributions in response to changing ocean conditions, the net impact of warming or cooling on predator–prey interactions was not determined a priori from the range extent of either predator or prey alone. For Atlantic cod, an historically dominant piscivore in the region, we found that both historical and future warming led to a decline in the proportion of prey species' range it occupied and caused a potential reduction in its ability to exert top‐down control on these prey. In contrast, the potential for overlap of spiny dogfish with prey species was enhanced by warming, expanding their importance as predators in this system. In sum, the decline in the ecological role for cod that began with overfishing in this ecosystem will likely be exacerbated by warming, but this loss may be counteracted by the rise in dominance of other piscivores with contrasting thermal preferences. Functional diversity in thermal affinity within the piscivore guild may therefore buffer against the impact of warming on marine ecosystems, suggesting a novel mechanism by which diversity confers resilience. Abstract : The degree to which warming might lead to changes in the intensity of interactions among species pairs in marine ecosystems has largely been untested. We find that warming‐induced declines in overlap between cod and prey create spatial refugia that may limit the potential for cod to exert top‐down control of prey populations. However, warming enhances the potential ecological importance of spiny dogfish, resulting in a reshuffling in the identity of the dominant piscivore. Changes in spatial overlap between key species in an ecosystem may serve as an early warning of future climate impacts on large marine ecosystems and a useful community‐level complement to recent species‐level assessments of climate. Diversity in thermal sensitivity within predator guilds may buffer the cascading consequences of warming on prey populations, suggesting a novel mechanism by which diversity confers resilience.